Clean Android Architecture : Take a Layered Approach to Writing Clean, Testable, and Decoupled Android Applications. - Dumbravan, Alexandru (Packt Publishing, Limited, 2022)
Learn how to build, maintain, and test Android applications using clean architecture principles Key Features Understand various software design principles and patterns to make an application more testable Structure your application's code into different layers and components to make it more maintainable and flexible Study popular libraries and frameworks and integrate them into an application Book Description As an application's code base increases, it becomes harder for developers to maintain existing features and introduce new ones. In this clean architecture book, you'll learn to identify when and how this problem emerges and how to structure your code to overcome it. The book starts by explaining clean architecture principles and Android architecture components and then explores the tools, frameworks, and libraries involved. You'll learn how to structure your application in the data and domain layers, the technologies that go in each layer, and the role that each layer plays in keeping your application clean. You'll understand how to arrange the code into these two layers and the components involved in assembling them. Finally, you'll cover the presentation layer and the patterns that can be applied to have a decoupled and testable code base. By the end of this architecture book, you'll be able to build an application following clean architecture principles and have the knowledge you need to maintain and test the application easily. What you will learn Discover and solve issues in Android legacy applications Become well versed in the principles behind clean architecture Get to grips with writing loosely coupled and testable code Find out how to structure an application's code in separate layers Understand the role each layer plays in keeping the application clean Integrate existing frameworks and libraries for each layer Who this book is for This book is for Android developers who want to learn about managing the complexity of their applications, and is also highly recommended for intermediate or advanced Android developers looking for a go-to guide for clean architecture and the integration of various Android technologies. New developers familiar with the fundamentals of Android app development will find this book useful too.